Impact of critical illness on continuation of anticancer treatment and prognosis of patients with aggressive hematological malignancies - Swann Bredin; Justine Decroocq; Clément Devautour; Julien Charpentier; Clara Vigneron; Frédéric Pène (Annals of Intensive Care, 2024)
Abstract Background Maintaining the dose-intensity of cancer treatment is an important prognostic factor of aggressive hematological malignancies. The objective of this study was to assess the long-term outcomes of intensive care unit (ICU) survivors with acute myeloid leukemia (AML) or aggressive B-cell non-Hodgkin lymphoma (B-NHL) with emphasis on the resumption of the intended optimal regimen of cancer treatment. Patients and methods We conducted a retrospective (2013–2021) single-center observational study where we included patients with AML and B-NHL discharged alive from the ICU after an unplanned admission. The primary endpoint was the change in the intended optimal cancer treatment following ICU discharge. Secondary endpoints were 1-year progression-free survival and overall survival rates. Determinants associated with modifications in cancer treatment were assessed through multivariate logistic regression. Results Over the study period, 366 patients with AML or B-NHL were admitted to the ICU, of whom 170 survivors with AML (n = 92) and B-NHL (n = 78) formed the cohort of interest. The hematological malignancy was recently diagnosed in 68% of patients. The admission Sequential Organ Failure Assessment (SOFA) score was 5 (interquartile range 4–8). During the ICU stay, 30 patients (17.6%) required invasive mechanical ventilation, 29 (17.0%) vasopressor support, and 16 (9.4%) renal replacement therapy. The one-year survival rate following ICU discharge was 59.5%. Further modifications in hematologic treatment regimens were required in 72 patients (42%). In multivariate analysis, age > 65 years (odds ratio (OR) 3.54 [95%-confidence interval 1.67–7.50], p < 0.001), ICU-discharge hyperbilirubinemia > 20 µmol/L (OR 3.01 [1.10–8.15], p = 0.031), and therapeutic limitations (OR 16.5 [1.83–149.7], p = 0.012) were independently associated with modifications in cancer treatment. Post-ICU modifications of cancer treatment had significant impact on in-hospital, 1-year overall survival and progression-free survival. Conclusion The intended cancer treatment could be resumed in 58% of ICU survivors with aggressive hematological malignancies. At the time of ICU discharge, advanced age, persistent liver dysfunction and decisions to limit further life-support therapies were independent determinants of cancer treatment modifications. These modifications were associated with worsened one-year outcomes.